Social Pressure: Motif dan Alasan Anak Melakukan Aborsi - Larasati, Yuniar Galuh; Abdullah, Irwan (Jurnal Community, 2023)
Social pressure is a phenomenon that often leads minors to choose abortion. Studies that have discussed this phenomenon only focus on the context of law enforcement, so they have not comprehensively explained the social pressure that drives children to have abortions. This study focuses on the question "How does social pressure encourage children to have abortions?". To answer this question, this study uses a descriptive qualitative approach to explore the narratives and motives of social pressure that encourage children to have abortions. The findings in this study show that abortion is a rational choice of the child in the face of social pressure from people close to the child emotionally, biologically, and structurally. This study recommends that the phenomenon of social pressure on child abortionists be explained by interviewing groups of children who have had abortions in order to gain a more comprehensive understanding of the phenomenon.